Call of the Individual; Privatise & Disinvest Parties Restructuring Around individual Probity - "Krishnatry, S M" (New Delhi, 2001)
Call of the individual calls for widespread debates in all legislature, panchyats and forums of the democratic world, no less by all medias. Political parties systems, being under retrospection, should also please respond coolly and patriotically. The call is the call of each individual by each individual and for each individual. Call of the individual is an alltime book like scriptures.
Keywords: Political Parties-India